A Mosquito Psorophora ferox (Humboldt 1819) (Insecta: Diptera: Culicidae) - Christopher J. Holderman; C. Roxanne Connelly (EDIS)
This document provides an in-depth profile of the mosquito species Psorophora ferox, commonly known as the white-footed woods mosquito. Native to North and South America, this mosquito is prevalent in woodland environments with intermittent pools. While it is not a major vector for human pathogens, it is known for its persistent and painful bites. The article details the mosquito’s life cycle, distribution, and medical significance, highlighting its role in transmitting certain viruses in laboratory settings. Management recommendations include avoiding outdoor activities during peak mosquito activity and using EPA-registered repellents.